GLOMERULAR PROSTAGLANDIN E2 IS UPREGULATED DURING ONSET OF ALBUMINURIA THAT IS SUPPRESSED AFTER DUAL BLOCKADE OF ITS EP2 AND EP4 RECEPTORS IN A RAT MODEL OF GLOMERULAR HYPERFILTRA. (June 2022) - Schulz, Angela; Mangelsen, Eva; Kourpa, Aikaterina; Kaiser, Debora; Rothe, Michael; Panakova, Daniela; Bolbrinker, Juliane; Kreutz, Reinhold
Abstract : Objective: Glomerular hyperfiltration (GH) is an important mechanism in the development of albuminuria in hypertension. Recent in vitro data indicated an activation of an autocrine/paracrine cyclooxygenase 2 (COX2)/prostaglandin E2 (PGE2) pathway resulting in podocyte injury in GH by using fluid flow shear stress exposure. This was mediated by concerted ignalling via both prostaglandin E2 receptors (EP), EP2 and EP4. Here, we explored the role to target this pathway in vivo by using a rat model with GH and albuminuria. Design and method: We used the Munich Wistar Frömter (MWF) rat model with an inherited nephron deficit as a model of GH and albuminuria. Because analysis of PGE2 levels in vivo is limited by conventional methods, we developed a modified liquid chromatography tandem mass spectrometry (LC/ESI-MS/MS) protocol to quantify PGE2 levels in glomerular tissue. We then assessed glomerular PGE2 during the onset of albuminuria in young MWF at 4 to 8 weeks of age. Furthermore, the renoprotective effects of either separate or combined pharmacological blockade of EP2 (by PF-04418948) and EP4 (by ONO-AE3-208) in MWF was explored. Treatment started at the onset of albuminuria at 4 weeks and was continued for 8 weeks. Results: During the onset of albuminuria, PGE2 levels were significantly elevated in isolated glomeruli of MWF at both 4 and 8 weeks of age (p < 0.01, respectively) as compared to albuminuria resistant spontaneously hypertensive rats (SHR). At 12 weeks of age, untreated MWF developed pronounced albuminuria, which was significantly, although modestly, reduced by separate EP2 or EP4 blockade. Remarkably, combined EP2 and EP4 blockade resulted in a significant suppression (-71%) of albuminuria in MWF at 12 weeks. Importantly, this pharmacological treatment did not affect systolic blood pressure and creatinine clearance (Figure 1). Conclusions: We demonstrated the activation of glomerular PGE2 in vivo in the setting of hyperfiltration and albuminuria in the MWF rat model. Dual EP2 and EP4 receptor blockade exhibited a marked suppression of albuminuria without affecting systemic blood pressure and glomerular filtration rate. These data support further translational research to explore this therapeutic option for renoprotection.